Enjeux politique, mémoriel, identitaire et religieux dans les sociétés post-marronnes de la Guyane française et du Surinam : les monuments historiques - Jean Moomou (Conserveries Mémorielles)
This article explores new "territories of memory" in Bushinengue societies, specifically the Boni and the Cottica-nengue. Their traditional social framework, went through the introduction of new radiophonic, audiovisual and printing technologies, and moreover, historical monuments and steles used by the new Bushinengue generation for the transmission of knowledge about the society’s recent history. However, this new strategy for the conservation of a collective memory is coupled with an instrumentalization of history and a staging of the past dedicated to political, identitary and religious agendas.